THE EFFECT OF FINANCIAL DISTRESS AND PROFITABILITY ON EARNING MANAGEMENT - Hanum, Naila; Wardhani, Dian Kusuma; Utami, Rahmawati Ayu Budi (DIPONEGORO UNIVERSITY, 2023)
This research aims to provide empirical evidence that is related to the effect of financial distress and profitability on earnings management. Earnings management is measured by the Jones Modified Model. Financial distress is measured by the Grover Model. Profitability is proxied by profit margin, return on assets, return on equity, and earnings per share. The research sample of this study is a consumer goods industry which is listed in Indonesia Stock Exchange 2015-2017. Purposive sampling was used as a sampling method and obtained 108 samples. The analysis technique used is panel regression analysis with Stata 14. The results of this study indicate that each of financial distress, return on equity, and earnings per share has an effect on earnings management while profit margin and return on assets do not affect earnings management.